Politik Hukum Kedudukan KPK Sebagai Lembaga Pemberantasan Korupsi di Indonesia - Riza Sirait; Ismaidar Ismaidar (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The corruption in Indonesia is increasing day by day. This is because there are still weaknesses in law enforcement agencies that are part of the problem of law enforcement. Therefore, institutional reform is needed through the formation of the KPK as an independent state institution. However, the KPK institution's journey is not easy. Various judicial examinations to the Constitutional Court regarding the position and authority of the KPK have been carried out. These decisions included: the Constitutional Court decision on number 012-016-019 / PUU-IV / 2006, number 19 / PUU-V / 2007, number 36 / PUU-XV / 2017, and number 37 / PUU-XV / 2017, and the most recent decision rejecting the request for formal and material review of Law Number 19 of 2019. According to several decisions made by the Constitutional Court, the development of the position of the KPK is a politics of law in eradicating corruption.